Coaches' perceptions of successfully working with junior tennis parents - Lauer, L.; Gould, D.; Rolo, C.; Jannes, C.; Pennisi, N. (Medicine and Science in Tennis, 2006)
The article reports results from two studies regarding coaches' perceptions on the most effective strategies for working effectively with junior tennis parents and recommendations for coaches and administrators. Emerging from focus groups and a national survey many strategies were thought to be useful, however, junior tennis coaches asserted that effective communication based on honest and open interaction and listening to parents were most useful. They also made a number of recommendations to coaches and administrators including that coaches proactively educate parents, and that coaches be trained to do such education.